Pressurised metered dose inhalers with spacers versus nebulisers for β-agonist delivery in acute asthma in children in the emergency department. Issue 9 (19th August 2005) - Boyd, R; Stuart, P
Abstract : Objectives: Wet nebulisers are widely used for β-2 agonist delivery in Australasian emergency departments (ED). An increasing body of work suggests that pressurised metered dose inhalers with spacers (pMDI-S) are as effective. This study aims to investigate the effect on admission rates, total time in the ED, and total time in hospital after initiation of routine pMDI-S treatment for mild to moderate asthma in children presenting to the ED. Methods: Children with a discharge diagnosis of asthma were identified over sequential 3 month time periods. In the first period, wet nebuliser treatment was routine and in the subsequent trial period pMDI-S treatment was instituted as routine. Admissions rates, total time in hospital, and total time in the ED were recorded for each group. Results: Admission rates fell significantly from 31% to 20.6% after routine use of pMDI-S treatment. There was a non-significant trend to an increase in total ED and total hospital times. Conclusion: Introduction of routine pMDI-S treatment in the paediatric ED results in a significant drop in admission rates but no significant change in total hospital times or total ED times.